2015
DOI: 10.1021/acs.biochem.5b00447
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dissection of Mycobacterium tuberculosis Integration Host Factor Reveals Novel Insights into the Mode of DNA Binding and Nucleoid Compaction

Abstract: The annotated whole-genome sequence of Mycobacterium tuberculosis indicated that Rv1388 (Mtihf) likely encodes a putative 20 kDa integration host factor (mIHF). However, very little is known about the functional properties of mIHF or organization of mycobacterial nucleoid. Molecular modeling of the mIHF three-dimensional structure, based on the cocrystal structure of Streptomyces coelicolor IHF-duplex DNA, a bona fide relative of mIHF, revealed the presence of Arg170, Arg171, and Arg173, which might be involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(33 citation statements)
references
References 71 publications
4
29
0
Order By: Relevance
“…Consistent with previous studies (23), it was found that the E. coli ⌬ihfA or ΔihfB cells were highly sensitive to MMS compared to the wild-type cells (Fig. 1B).…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Consistent with previous studies (23), it was found that the E. coli ⌬ihfA or ΔihfB cells were highly sensitive to MMS compared to the wild-type cells (Fig. 1B).…”
Section: Resultssupporting
confidence: 92%
“…To understand the functional importance of the extra 86 amino acid residues at the N terminus of mIHF, we prepared two derivatives of mIHF, a truncated derivative containing the N-terminal 86 amino acid residues (pMtihfntd) and a C-terminal derivative lacking the 86 amino acids from the N terminus (pMtihfctd). These vectors encoding either the N-terminal (mIHF-NTD) or C-terminal (mIHF-CTD) regions of mIHF were tested for their ability to suppress the sensitivity of E. coli ⌬ihfA or ΔihfB cells using a previously established complementation assay (23). Wild-type (WT) E. coli ihfA or ihfB strains treated with methyl methanesulfonate (MMS) and UV served as positive controls.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations